Penanaman Mangrove demi Menjaga Ekosistem Wilayah Pesisir di Negeri Tulehu - Botanri, Adnan Affan Akbar; Pinontoan, Victhoritha; Dumatubun, Vera; Picauly, Analisye; Resmol, Paula; Berhitu, Pieter Thomas; Nanlohy, Willem Dominggus; Ohorella, Faud Hasan (Universitas Pattimura, 2024)
Community service activities are a tri dharma obligation for an academic. Coastal areas are transitional areas between the ocean and land, which contain various ecosystems, one of which is mangroves. There are various functions of mangroves, some of which are to maintain air quality and coastal ecosystems. The condition of mangroves in Indonesia is currently tending to worsen because they are not maintained and have changed functions. So the purpose of this community service activity is to add mangrove plants that will contribute to improving and maintaining air quality and coastal ecosystems. The location chosen is Wababe Beach, precisely in Negeri Tulehu because in that location there are many mangroves that have died and need to be replanted. Some of the things done in this community service activity are to first meet with the King of Negeri Tulehu. Then a review of the activity location was carried out. After that, the handover of 500 mangrove seedlings obtained from the Maluku Provincial Agriculture Office. The last planting activity was carried out by all participants at the designated location. The conclusion of this activity is that the activities carried out are right on target and answer the needs of residents for the addition of mangroves in coastal areas so that they can improve and maintain the quality of air and the ecosystem of coastal areas.